Whole-exome sequencing reveals POLR3B variants associated with progeria-related Wiedemann-Rautenstrauch syndrome - Shao-Wen Wu; Lin Li; Fan Feng; Li Wang; Yuan-Yuan Kong; Xiao-Wei Liu; Chenghong Yin (BMC, 2021)
Abstract Background Wiedemann-Rautenstrauch syndrome (WRS) is a rare autosomal recessive neonatal progeroid disorder characterized by prenatal and postnatal growth retardation, short stature, a progeroid appearance, hypotonia, and mental impairment. Case presentation A 6-year-old patient, who initially presented with multiple postnatal abnormalities, facial dysplasia, micrognathia, skull appearance, hallux valgus, and congenital dislocation of the hip, was recruited in this study. The patient was initially diagnosed with progeria. The mother of the patient had abnormal fetal development during her second pregnancy check-up, and the clinical phenotype of the fetus was similar to that of the patient. Whole-exome sequencing (WES) of the patient was performed, and POLR3B compound heterozygous variants-c.2191G > C:p.E731Q and c.3046G > A:p.V1016M-were identified in the patient. Using Sanger sequencing, we found that the phenotypes and genotypes were segregated within the pedigree. These two variants are novel and not found in the gnomAD and 1000 Genomes databases. The two mutation sites are highly conserved between humans and zebrafish. Conclusions Our study not only identified a novel WRS-associated gene, POLR3B, but also broadened the mutational and phenotypic spectra of POLR3B. Furthermore, WES may be useful for identifying rare disease-related genetic variants.